Islamic micro-financing schemes among financial institutions - WARSAME, M.H (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The present study aims to identify the importance of Islamic micro-financing schemes among the financial institutions and also determine the knowledge and attitudes of the respondents towards Shari’ah based financial products. A mixed-method approach, including quantitative and qualitative designs, has been employed by recruiting 255 and 15 respondents, respectively. The results showed no significant differences between respondents’ knowledge and access to Shari’a-compliant finance. Similarly, there were no significant differences between respondents depending on their length of stay in the UK, ethnicity, and employment status. Moreover, this required financial support and empowerment from the government and related institutions.